Fluid-solid-electric energy transport along piezoelectric flags. Issue 1 (4th March 2017) - Xia, Yifan; Doaré, Olivier; Michelin, Sébastien
Abstract: The fluid–solid–electric dynamics of a flexible plate covered by interconnected piezoelectric patches in an axial steady flow are investigated using numerical simulations based on a reduced-order model of the fluid loading for slender structures. Beyond a critical flow velocity, the fluid–solid instability results in large amplitude flapping of the structure. Short piezoelectric patches positioned continuously along the plate convert its local deformation into electrical currents that are used within a single internal electrical network acting as an electric generator for the external output circuit. The relative role of the internal and external impedance on the energy harvesting of the system is presented and analysed in the light of a full modelling of the electric and mechanical energy exchanges and transport along the structure.